'I have to hear them before I hear myself': developing therapeutic conversations in British counselling students. Issue 3 (2nd July 2016) - Lee, Billy; Prior, Seamus
Abstract: Transcripts of interviews from six students who had just completed a one-year postgraduate certificate in counselling skills were subjected to a qualitative analysis that focused on their accounts of the therapeutic action of talking and listening. The course offered a dialogue between psychodynamic and person-centred theoretical orientations. Interpretative phenomenological analysis, the methodology employed to make sense of their experience offers a dialogue between interpretative and phenomenological philosophical stances, thus mirroring the task faced by the students. Three themes with associated subthemes were surfaced: (1) Therapeutic openness captured the students' understandings of how the phenomenological principle of openness is experienced in practice; (2) Hearing beyond discourse reflected how their listening deepened during the course; (3) Presence reflected the changing quality of the encounter between the self and the other. These findings reflect British counselling students' lived experiences of listening and talking in their developing practice. We connect these results to broader themes of theory and research into the role of language in therapeutic conversations.